Implications of Financial Performance and Corporate Governance on Sustainability Report Disclosure - Pertiwi, Lulu Kusuma; Kusumawati, Eny (Universitas Muhammadiyah Surakarta, 2022)
This study aims to analyze profitability, leverage, firm size, and the board of directors on the sustainability report (SR) disclosure. The indicator used to measure SR disclosure was the GRI standard index (2018). The population in this study involved companies listed in the Asia Sustainability Reporting Rating (ASRR). The sample selection method employed purposive sampling, with a total sample of 189 data. The data were obtained using secondary data from the annual report and sustainability report for the 2016-2020 period. The analytical method utilized was multiple linear regression analysis. The study results empirically proved that profitability, leverage, firm size, and the board of directors affected the disclosure of sustainability reports.